POTENCY OF CHLORELLA SPP. AS AN ANTIOXIDANT AND ANTI-INFLAMMATORY AGENT - Cahyani, Fauzia Rahma; Isman, Hasna Siti Munifah (Journal of Vocational Health Studies, 2022)
Background: Chlorella is a natural marine product that belongs to the type of unicellular green microalgae which is currently widely used as an alternative therapy because of its secondary metabolite content which has various benefits with minimal side effects. Chlorella has also been widely studied for activities such as being an antioxidant and anti-inflammatory agent that plays a role in prevention and treatment. Purpose: This literature review aims to dig up information about the potency of Chlorella as an antioxidant and anti-inflammatory agent based on several previous studies. Review: Based on the online existing literature from the PubMed and Google Scholar databases, the results of studies on the potential of Chlorella as an antioxidant and anti-inflammatory agent were analyzed. Based on the literature review, Chlorella can act as an antioxidant and anti-inflammatory agent due to the phenolic compounds, carotenoid pigments and chlorophyll, and extracellular polysaccharides (EPS) contained in it. Conclusion: Chlorella has antioxidant and anti-inflammatory activity and has the potential to prevent and treat several types of diseases.